Rococo en neoclassicisme : van De Munt tot Fort Napoleon - Heirman, Michiel, 1951-; Van de Vijver, Dirk, 1969- (Tielt : Lannoo, 2008)
Luik, Gent, Lier, Hoegaarden, Antwerpen, Le Roeulx, Namen, Brugelette, Saint-George-sur-Meuse - Brussel, Lokeren, Seneffe, Herstal, Harelbeke, Heers, Floreffe, Verviers, Sint-Truiden, Bornem, Wortegem-Petegem, Kortrijk, Oostende, Waasmunster, Waremme, Boussu, La Louvière/ Brussel
Keywords: Neoclassicisme; Rococo